When finding terms, you must substitute in the term you need to find for n. So, to find the second term, you would do a(2)=5+(2-1)(7), and after solving the answer should be 13. To find the fifth term, it’s a(5)=5+(5-1)(7). After solving that would equal 33. Try the next one to see if you understand it, it’s mostly substituting numbers for n and solving! I hope I helped :)
To find the second term, replace every n with 2 and use PEMDAS to simplify a(n) = -5+(n-1)(7) a(2) = -5+(2-1)(7) a(2) = -5+(1)(7) a(2) = -5+7 a(2) = 2 The second term is 2
Similarly, plug in n = 5 to get the fifth term a(n) = -5+(n-1)(7) a(5) = -5+(5-1)(7) a(5) = -5+(4)(7) a(5) = -5+28 a(5) = 23 The fifth term is 23
Finally, replace every n with 9 to find the ninth term a(n) = -5+(n-1)(7) a(9) = -5+(9-1)(7) a(9) = -5+(8)(7) a(9) = -5+56 a(9) = 51 The ninth term is 51